Culture – Knowledge – Innovation - Loudín, Jiří (Teorie vědy / Theory of Science, 2010)
The article presents an overview of the research problems that frame the conceptual context of the project “Transition form imitations to innovations as social and cultural process”. The title of the project indicates a main perspective of the analysis. The current rise of knowledge society is a complex process in which so far unconnected elements are being connected. Culture, innovation, and knowledge and their interactions are identified as the key agents of the followed process. The role of culture in knowledge and innovation has been so far underestimated, although intuitively it has always been perceived as crucial. In this respect, the issue of transfer – let it be technological, institutional, or cultural transfer – deserves a foremost research attention. The same applies to the spatial dimension of culture – innovation – knowledge interactions, as these gain a new relevance and meaning in the context of globalization and regionalization.